Temperature-dependent nitrogen configuration of N-doped graphene by chemical vapor deposition. (January 2015) - Sui, Yanping; Zhu, Bo; Zhang, Haoran; Shu, Haibo; Chen, Zhiying; Zhang, Yanhui; Zhang, Yaqian; Wang, Bin; Tang, Chunmiao; Xie, Xiaoming; Yu, Guanghui; Jin, Zhi; et al.
Abstract: The N-doped graphene domain is synthesized through co-growth of ammonia and methane by chemical vapor deposition (CVD). Results showed that the nitrogen concentration, defect density, and doping level increased with the decrease in growth temperature. Notably, the position of N1s main peak from X-ray photoelectron spectroscopy (XPS) showed a significant linear blueshift as the temperature decreased, indicating that the main doping nitrogen configuration gradually evolved from pyridinic N to pyrrolic N consistent with the theoretical explanation. In addition, the nitrogen configuration was not influenced by the NH3 flow rate, which was mainly pyridinic N at the high temperature. With increasing NH3 flow rate the redshift of the Raman peak was caused by the elongation of the CC bonds. This work presented a process to control the predominant bonding configuration of doping nitrogen by mainly choosing the growth temperature through CVD.